Program Edukasi Dan Praktik Kerajinan Keychain Untuk Meningkatkan Kreativitas Anak Yayasan Mizan Amanah Krukut - Widiya Shantika; Kaesa Fadillah Rahma; Tasya Amelia (Journal of Conflict and Social Class (JCSC), 2025)
The Keychain Craft Education and Practice Program aims to enhance the creativity of children at the Mizan Amanah Krukut Foundation through hands-on activities in making keychain handicrafts using pipe cleaner materials. This program was designed as an engaging and accessible creative learning activity to develop fine motor skills, imagination, and self-confidence among children. The implementation method consisted of a brief educational session introducing the materials and basic crafting techniques, followed by guided group practice facilitated by instructors. The materials used in this activity included colorful pipe cleaners, keychain rings, small pliers, glue, and scissors. The program was conducted on Friday, November 21, 2025, with a total working duration of approximately 3 hours, covering the explanation session, crafting process, and evaluation of the finished products. The results indicated that the children were able to create various creative keychain designs based on their individual ideas and showed high enthusiasm and improved creativity throughout the activity. Therefore, this program is expected to serve as an effective and sustainable educational approach in supporting creative development for children within the foundation.